Comment on "Fragmentation of the Adriatic Promontory: New Chronological Constraints From Neogene Shortening Rates Across the Southern Alps (NE Italy)" by Moulin & Benedetti. Issue 7 (26th July 2021) - Poli, M. E.; Monegato, G.; Fontana, A.; Mozzi, P.; Rossato, S.; Zampieri, D.; Falcucci, E.; Gori, S.; Caputo, R.; Zanferrari, A.
Abstract: Moulin and Benedetti (2018), https://doi.org/10.1029/2018TC004958 present a new interpretation of the Neogene‐Quaternary tectonic evolution of the Eastern Southern Alps (ESA) in Veneto‐Friuli. After the reinterpretation of literature field data by means of remote sensing analysis (Digital Elevation Model interpretation), they calculated deformation rates of the tectonic structures through age interpretation of geomorphological surfaces of the Veneto‐Friuli piedmont plain. The authors linked the result of surface analysis to the thrust and fold architecture of the ESA basing on the Castellarin et al. (2006), https://doi.org/10.1016/j.tecto.2005.10.013 interpretation of TRANSALP project and the Friuli geological map at the scale 1:150, 000 (Carulli, 2006). Discussing their new architecture of the ESA, the authors finally yielded rates of Europe‐Adria plates convergence and suggested fragmentation of Adria over the last 1–2 Ma. The present comment is aimed at discussing several critical points concerning: the use of the geomorphological and chronological data; the misinterpretation of the Digital Terrain Model; the reconstruction of the balanced geological cross section. Moreover, the application of a structural model defined in a certain area to another without considering peculiar structural complexities available in the literature results is geologically and methodologically questionable. Plain Language Summary: The late Quaternary sedimentary successions of Eastern Southern Alps (ESA) recorded important deformations related to the ongoing Europe/Adria collision. Their chronology has been updated in the last years, thanks to detailed surveys and analyses. Our knowledge on the tectonic architecture of the ESA has been recently improved by the new Geological maps of Italy (CARG Project: Zanferrari, Avigliano, Monegato, et al., 2008, Zanferrari, Avigliano, Grandesso, et al., 2008; Zanferrari et al., 2013). However, the bulk of the tectonic and chronological data was discarded or improperly used in Moulin and Benedetti (2018), https://doi.org/10.1029/2018TC004958 in their estimate of the shortening and associated rates and hence in the subsequent discussion on the fragmentation of Adria. Key Points: The chronological constraints and the shortening rates derive from misreading of the available literature and not from new original data The description of the tectonic structures do not consider updated geological information available for the study area The balanced cross‐section is inconsistent with the major crustal models for the Eastern Southern Alps, no alternate discussion is provided